Dampak Positif Pembelajaran Online Dalam Sistem Pendidikan Indonesia Pasca Pandemi Covid-19 - Yulita Pujilestari (ADALAH, 2020)
Abstract:The rapid development of Information Technology especially the internet opens opportunities for the development of better information services in educational institutions. After the outbreak of the 19th pandemic to Indonesia in mid-March 2020, the local government issued a policy in the world of education, which is to temporarily eliminate direct face-to-face learning and is replaced by online learning, both at the elementary and secondary school level, and at the university level. This was realized in a system called an electronic university (e-University).Keywords: Information Technology Development, Education, Online Learning Abstrak: Pesatnya perkembangan Tekhnologi Informasi terutama internet membuka peluang bagi pengembangan layanan informasi yang lebih baik di lembaga pendidikan. Pasca mewabahnya pandemi covid 19 ke Indonesia pada pertengahan maret 2020 maka pemerintah daerah mengeluarkan kebijakan dalam dunia pendidikan yaitu meniadakan sementara pembelajaran tatap muka secara langsung dan diganti dengan pembelajaran secara online, baik pada tingkat sekolah dasar dan menengah, maupun tingkat perguruan tinggi. Hal itu diwujudkan dalam suatu sistem yang disebut electronic university (e-University).Kata Kunci: Perkembangan Teknologi Informasi, Pendidikan, Pembelajaran Online